2012
DOI: 10.1097/jom.0b013e318249202d
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index As a Predictor of Firefighter Injury and Workers' Compensation Claims

Abstract: Objective To determine the relationship between lifestyle variables including body mass index (BMI) and filing a worker’s compensation claim due to firefighter injury. Methods A cross-sectional evaluation of firefighter injury related worker compensation claims occurring 5 years after the original PHLAME study intervention. Results Logistic regression analysis for variables predicting filing a worker’s compensation claim due to an injury were performed. with a total of 433 participants. The odds of filing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…A recent longitudinal study [Jahnke et al, 2013] reported that obese firefighters are 5.2 times more likely to experience musculoskeletal injuries than non-obese firefighters. According to another study [Kuehl et al, 2012], obese firefighters are 2.9 times more likely to file workers' compensation claims than non-obese firefighters. Team sports at fire stations have great potential to be leveraged for the prevention of CVD and even injuries in firefighters who are also an inherently competitive group/ occupational culture.…”
Section: Implications For Prevention Of Obesity Among Professional Fimentioning
confidence: 97%
See 1 more Smart Citation
“…A recent longitudinal study [Jahnke et al, 2013] reported that obese firefighters are 5.2 times more likely to experience musculoskeletal injuries than non-obese firefighters. According to another study [Kuehl et al, 2012], obese firefighters are 2.9 times more likely to file workers' compensation claims than non-obese firefighters. Team sports at fire stations have great potential to be leveraged for the prevention of CVD and even injuries in firefighters who are also an inherently competitive group/ occupational culture.…”
Section: Implications For Prevention Of Obesity Among Professional Fimentioning
confidence: 97%
“…About 1.2 million firefighters are among the occupational groups with high obesity prevalence in the US [Caban et al, 2005;Choi et al, 2011;Haddock et al, 2011;Gu et al, 2014] and are at high risk of on-duty cardiovascular disease (CVD) mortality [Kales et al, 2007;Geibe et al, 2008]. At the same time, they are also at higher risk for workrelated injuries [Poplin et al, 2012;Jahnke et al, 2013] also associated with obesity or aerobic fitness level [Kuehl et al, 2012;Jahnke et al, 2013;Poplin et al, 2014].…”
Section: Introductionmentioning
confidence: 97%
“…To address this issue, Figure 3 presents 19 obesity prevalence data points from 6 studies based on nationally representative data (16,38,39,46,53,64) and shows that between 1986 and 2011 workforce obesity prevalence doubled from ∼15% to ∼30%. Figure 2 shows a cluster of studies with above-average obesity prevalence data among firefighters (7,35,83,112), although lower estimates were also reported (33,60). A cluster of studies for the military showed below-average estimates (49,65,107).…”
Section: Obesitymentioning
confidence: 99%
“…Studies included reflect nationally representative samples (16,17,38,39,46,53,64,123) as well as those that are specifically focused on firefighters (7,33,35,60,83,106,112), police (law enforcement) (101,114), the military (49, 65, 107), or generally employed …”
Section: Fitness Profile Of the Us Workforcementioning
confidence: 99%
“…Indeed, the heaviest workers file twice as many health claims as workers of normal weight with cost and number of days lost being strongly associated with BMI (Ostbye et al 2007). Interestingly, health claims of obese workers were even higher in high-risk occupations with high physical demands and ergonomic stress (Ostbye et al 2007;Kuehl et al 2012). Ultimately, obesity is reported to reduce participation in the workforce (Degli Esposti et al 2006) and is associated with increased absenteeism, disability, and health claims (Han et al 2009) as well as attenuated salaries (Baum et al 2004) and productivity (Bhattacherjee et al 2003), with a 13-fold increase in lost working days and 11-fold increase in compensation claims (Tunceli et al 2006).…”
Section: Impact Of Chronic Health Disorders On Physical Functionmentioning
confidence: 99%